Recurrent solitary fibrous tumour in the cerebellopontine angle - (:unkn) unknown (ELSEVIER SCI LTD, 2005)
Solitary fibrous tumours (SIFT) of the central nervous system are rare. They resemble meningioma in clinical presentation, imaging features and appearance at surgery. Schwannoma, hemangiopericytoma and other spindle cell mesenchymal neoplasms should also be considered in the differential diagnosis. Although the histogenesis of this tumour is still debated, strong CD34 reactivity of the tumour cells suggests that SFT is mesenchymal. We present the clinical, radiological, and pathological features of an SFT located in the cerebellopontine angle (CPA). A 55-year-old female presented with 6 months of headache. The MRI scan showed a contrast enhancing :ovoid mass in the left CPA. At craniotomy, the tumour was completely resected. Histolopathological diagnosis was of meningioma. Three years later, the symptoms recurred and an MRI scan demonstrated tumour recurrence. A repeat craniotomy was performed and the lesion was again completely excised. Tumour morphology on histopathology and immunoreactivity for CD34 of the tumour cells supported the diagnosis of SFT. Review of the original tumour also disclosed immunoreactivity for CD34. Ki67 labeling indices were less than 1% in both tumours.(c) 2005 Elsevier Ltd. All rights reserved.
Keywords: meningioma; schwannoma; solitary fibrous tumour; OF-THE-LITERATURE; SPINAL NERVE ROOTLET; MENINGES; CORD; HEMANGIOPERICYTOMA; FEATURES; GLAND